FORCED COOLING OF BRAKE FRICTION UNITS (part 2) - Kindrachuk, Myroslav; Volchenko, Dmytro; Voznyi, Andrii; Andreychikov, Yevgen; Vudvud, Oleksandr; Skochko, Serhii (Problems of Friction and Wear, 2024)
Experimental design developments and theoretical studies of disk (tubular type) - shoe brakes of drilling winches with forced nano-liquid cooling in any state of the unit allowed: to propose a workable design of a tubular-type disk-shoe brake, which is a new direction in brake engineering for drilling equipment, since it has increased energy capacity; to divide the functions between the main and additional disks, the first is a brake, and the second is a heat exchanger; based on the thermal balance of the main brake disk, determine the heat exchange surface area of ​​the additional disk; to connect the volumes of the chambers of the main and additional disks with each other by diffusers and confusers located on semicircles, which are a kind of accelerators and retarders of heat exchange processes; to make the brake disc friction belt thin-walled and thus ensure minimal surface-volume temperature gradients during frictional electrothermomechanical interaction with the linings, and as a consequence, small equivalent stresses.